Tanacetum species: Bridging empirical knowledge, phytochemistry, nutritional value, health benefits and clinical evidence - Khatib, Sohaib; Sobeh, Mansour; Faraloni, Cecilia; Bouissane, Latifa (Frontiers in Pharmacology, 2023)
Introduction: The Tanacetum genus consists of 160 accepted flowering species thriving throughout temperate regions, mainly in the Mediterranean Basin, Northern America, and southwestern and eastern Asia. Tanacetum species bear a long-standing record of use in the folk medicine of indigenous tribes and communities worldwide, along with multitudinous applications in traditional cuisines, cosmeceuticals, and agricultural fields. Methods: Up-to-date data related to traditional uses, phytochemistry, biological activities, toxicity and clinical trials of the genus Tanacetum were systematically reviewed from several online scientific engines, including PubMed, Web of Science, Scopus, SciFinder, Wiley Online, Science Direct, and Cochrane library. Results and discussion: Over the past three decades, 241 metabolites have been isolated from nearly twenty species, including phenolic acids, flavonoids, coumarins, fatty acids and alkanes, aldehydes, volatile compounds, and naphthoquinones. Some unique metabolites have also been identified, such as the ceramides tanacetamide (A-D) from T. artemisioides, pyrethrins from T. cinerariifolium, and sesquiterpene lactones from several species. However, these secondary metabolites are still poorly studied despite in vitro clues highlighting their colossal pharmacological properties, especially as hypotensive, neuroprotective, anticancer, and antimicrobial agents. Scientific studies have validated some traditional claims of the plant, such as antidiabetic, anticancer, anthelmintic, insecticide, antioxidant, and hepatoprotective activities, as well as against festering wounds, skin ulcers, urinary tract infections, and sexually transmitted diseases. Other ethnomedicinal uses for arthritis, gout, rheumatism, anemia, and as a litholytic, antivenom and diaphoretic have not yet been supported and would constitute the subject of further research.